2003
DOI: 10.1080/07060660309507081
|View full text |Cite
|
Sign up to set email alerts
|

Control, byBrassicaseed pomace combined withPseudomonas boreopolis, of damping-off of watermelon caused byPythiumsp.

Abstract: A total of 57 isolates of fungi, bacteria, and actinomycetes were screened for their ability to degrade the glucosinolate sinigrin. Pseudomonas boreopolis was the most effective among 26 isolates having the capacity to degrade sinigrin. Treatment with ground Brassica seed pomace and Pseudomonas boreopolis resulted in the release of volatile compounds. Gas-chromatography analyses allowed to identify allyl isothiocyanate and 3-butenyl isothiocyanate as the major volatile compounds released from enzymatic hydroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…In our research, laboratory studies and field experiments showed that AITC used as a pre‐plant soil fumigant can effectively control certain soil‐borne bacteria and fungi, nematodes and weeds. AITC is reported to control R. solani , V. dahlia , F. oxysporum , P. aphanidermatum and P. capsica , as also confirmed in our dose–response tests. In addition, we found that AITC has high fumigation biological activity against R. solanacearum , which means that AITC has the potential to control bacterial wilt in the nightshade family.…”
Section: Discussionsupporting
confidence: 89%
“…In our research, laboratory studies and field experiments showed that AITC used as a pre‐plant soil fumigant can effectively control certain soil‐borne bacteria and fungi, nematodes and weeds. AITC is reported to control R. solani , V. dahlia , F. oxysporum , P. aphanidermatum and P. capsica , as also confirmed in our dose–response tests. In addition, we found that AITC has high fumigation biological activity against R. solanacearum , which means that AITC has the potential to control bacterial wilt in the nightshade family.…”
Section: Discussionsupporting
confidence: 89%
“…Olivier et al (1999) found that 2-propenyl ITC was the major compound released by B. nigra with concentrations of 0.4-3.5 mg 2-propenyl ITC g À1 dw of tissue and confirmed its fungicidal activity toward Verticillium dahliae and Helminthosporium solani. 2-propenyl ITC and 3-butenyl ITC are toxic to some fungal plant pathogens, such as R. solani AG4, Sclerotium rolfsii, Sclerotinia sclerotiorum, Pythium aphanidermatum and Phytophthora capsici (Chung et al 2003). In our experiment, the highest concentrations of ITCs extracted from soil occurred in the first few days.…”
Section: Discussionmentioning
confidence: 76%
“…Due to the toxicity of ITCs, it may be used instead of conventional pesticides for the inhibition of soil-borne pathogens (Smith and Kirkegaard 2002). Such pathogens include Verticillium dahliae, Helminthosporium solani, Sclerotium rolfsii, Sclerotinia sclerotiorum and Phytophthora capsici (Chung et al 2003). However, little is known about the effect of biofumigants on the natural soil microbial communities required to maintain soil functions.…”
Section: Introductionmentioning
confidence: 98%